Bootstrability in defect CFT: integrated correlators and sharper bounds - Andrea Cavaglià; Nikolay Gromov; Julius Julius; Michelangelo Preti (Journal of High Energy Physics, 2022)
Abstract We continue to develop Bootstrability — a method merging Integrability and Conformal Bootstrap to extract CFT data in integrable conformal gauge theories such as N $$ \mathcal{N} $$ = 4 SYM. In this paper, we consider the 1D defect CFT defined on a 1 2 $$ \frac{1}{2} $$ -BPS Wilson line in the theory, whose non-perturbative spectrum is governed by the Quantum Spectral Curve (QSC). In addition, we use that the deformed setup of a cusped Wilson line is also controlled by the QSC. In terms of the defect CFT, this translates into two nontrivial relations connecting integrated 4-point correlators to cusp spectral data, such as the Bremsstrahlung and Curvature functions — known analytically from the QSC. Combining these new constraints and the spectrum of the 10 lowest-lying states with the Numerical Conformal Bootstrap, we obtain very sharp rigorous numerical bounds for the structure constant of the first non-protected state, giving this observable with seven digits precision for the ’t Hooft coupling in the intermediate coupling region λ 4 π ~ 1 $$ \frac{\sqrt{λ }}{4π}\sim 1 $$ , with the error decreasing quickly at large ’t Hooft coupling. Furthermore, for the same structure constant we obtain a 4-loop analytic result at weak coupling. We also present results for excited states.